Value of the application of the heart rate performance curve in sports - Hofmann, P.; Pokan, R. (International Journal of Sports Physiology and Performance, 2010)
The heart rate performance curve (HRPC) has been shown to be nonlinearly related to work load. This phenomenon has been used to determine a deflection point and to be related to the lactate anaerobic threshold. The original method was heavily criticized, and the method was challenged by several authors. However, some authors also demonstrated a high value for this method`s application in various sports conditions. Unfortunately, the HRPC was shown to be not uniform and three different patterns were found. Basic investigations have shown a dependence of the HR-deflection on beta-1-receptor sensitivity, which gave a plausible explanation of the phenomenon. Important details regarding the testing protocol and the method of turn point determination are given in this review. As a conclusion, we may state that based on numerous studies the method is plausible and valid to determine aerobic exercise performance in various laboratory ergometer and specific sports-related field conditions. Standard protocol conditions adjusted to the exercise performance level of subjects and a computer-supported determination of turn points are necessary to obtain reliable results. Large-scale investigations to validate the heart rate turn point with maximal lactate steady state are still needed. However, from the available literature, the application of this noninvasive method can be recommended to determine aerobic exercise performance in various sports. This noninvasive test is easy to perform repeatedly, which gives interesting possibilities for the monitoring of training adaptation in the short term, such as altitude training or specific taper forms.